Masuknya Peradaban Islam ke Indonesia dan Peran Walisongo dalam Proses Islamisasi Nusantara - Shelfiya Anjani (STIKes Ibnu Sina Ajibarang, 2024)
Broadly speaking, there are three theories about the arrival of Islam to Indonesia, namely the Gujarat theory, the Arabic theory and the Persian theory. The arrival of Islam to various regions in Indonesia did not occur simultaneously. Likewise, the various regions and kingdoms he visited had opposing socio-cultural and political conditions. Historians agree that Sumatra was the region where Islam first visited. The word wali songo is a combination of